Correlation of axial impact forces with knee joint forces and kinematics during simulated ski-landing - Yeow, C. H.; Kong, C.-Y.; Lee, P. V. S.; Goh, J. C.-H. (Journal of Sports Sciences, 2011)
Anterior cruciate ligament (ACL) rupture, during ski-landing, is caused by excessive knee joint forces and kinematics, like anterior tibial translation, internal tibial rotation, and valgus rotation. It is not well understood how these forces/kinematics are directly related to ski-landing impact. In the present study, we applied simulated ski-landing impact to knee specimens, and examined joint force/kinematic responses and their correlations with impact force. Ten human cadaveric knees were subjected to axial impact loading at 70° of flexion to simulate ski-landing impact. Impact was repeated with incremental magnitude until ACL failure. Axial impact forces, anterior-posterior and medial-lateral tibial forces were measured using a tri-axial load cell. Anterior-posterior tibial translation, internal-external tibial rotation, and valgus-varus rotation were determined using a motion-capture system. We found positive correlations of axial impact force with anterior tibial force, medial tibial force, anterior tibial translation, internal tibial rotation, and valgus joint rotation. Axial impact forces were more strongly correlated with anterior tibial forces (R 2 = 0.937 ± 0.050), anterior tibial translation (R 2 = 0.916 ± 0.059), and internal tibial rotation (R 2 = 0.831 ± 0.141) than medial tibial force (R 2 = 0.677 ± 0.193) and valgus joint rotation (R 2 = 0.630+0.271). During ski-landing, these joint forces/kinematics can synergistically act to increase ACL injury risk, whereby the failure mechanism would be dominated by anterior tibial forces, anterior tibial translation, and internal tibial rotation.